Self-resetting viscoelastic energy consumption coupling beam device - ZHU RUIZHAO; XIE LINLIN; ZHANG ZHENHUA; XU GANG; GUO TONG (2024)
The invention relates to a self-resetting viscoelastic energy dissipation coupling beam device which is composed of a left coupling beam limb (1), a right coupling beam limb (2), a left shear plate (3), a right shear plate (4), a viscoelastic material layer (5), a self-resetting mechanism (6) and an overload protection mechanism (7). Compared with the prior art, the coupling beam has the advantages of being capable of dissipating earthquakes in a wide frequency domain, excellent in deformability, capable of controlling peak displacement, residual displacement and peak acceleration of a structure at the same time, easy to replace and the like. 本发明涉及一种自复位黏弹性耗能连梁装置，其由左连梁肢(1)、右连梁肢(2)、左剪切板(3)、右剪切板(4)、黏弹性材料层(5)、自复位机构(6)和过载保护机构(7)组成。与现有技术相比，该连梁具有可在宽频域内耗散地震能力、优良变形能力、可同时控制结构的峰值位移、残余位移和峰值加速度、易更换等优点。